Employment under civil law contracts – selected issues - Ludera-Ruszel, Agata (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
This paper offers an analysis of the selected issues of employment under civil law contracts. Due to the differences existing in the national legislation between employee and non-employee employment the use of civil law contract as a basis for employment has major social implications. At the same time, this issue remains extremely up-to-date due to the persistent scale of civil law contracting in place of traditionally concluded contracts of employment.